MEMBONGKAR EKSTRIMISME; KEBEBASAN LIYAN DI RUANG PENDIDIKAN, SOSIAL - Alfederikus Efim (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2022)
The focus of this paper is on the forms of extremism in the social and educational spheres. The problems that often occur to color the Indonesian nation so far have always been related to the majority and minorities regarding their existence. Incidents of discrimination, isolating truths in certain groups also play a role and become a threat to the pluralistic existence of the Indonesian nation. This study uses a descriptive analytical method with a critical paradigm and literature study as a comparative reference. It aims to find and unravel the causes of forms of discrimination. Incidents of discrimination are strongly opposed because they are not in accordance with human nature as being related, also requires others. In the context of the life of the Indonesian people, the process of becoming a real human being is the main thing to know oneself, and to know others in the educational and social sphere. Generations of nations need to be breathed with teachings that will lead them to find true wisdom as humans who are capable of humanizing others. Educational and social space becomes very important for the growth of every human being who is able to see, understand lyan in a transcendent face